Potential of photodynamic therapy using polycationic photosensitizers in the treatment of lung cancer patients with SARS-CoV-2 infection and bacterial complications: Our recent experience - Gennady Meerovich; Evgeniya Kogan; Igor Romanishkin; Nikolay Zharkov; Sofiya Avraamova; Elena Shchelokova; Ekaterina Akhlyustina; Marina Strakhovskaya; Irina Meerovich; Sofya Demura; Irina Tiganova; Yulia Romanova; et al. (Photodiagnosis and Photodynamic Therapy)
The problem of treating cancer patients with lung cancer has become more difficult due to the SARS-CoV-2 viral infection and concomitant bacterial lesions. The analysis shows that the photodynamic effect of long-wavelength polycationic photosensitizers suppresses the tumor process (including the destruction of cancer stem cells), SARS-CoV-2 coronavirus infection, Gram-positive and Gram-negative bacteria, including those that can cause pneumonia. Therefore, the photodynamic approach using such photosensitizers is promising for the development of an effective treatment method for patients with lung cancer, including those with SARS-CoV-2 infection and bacterial complications.